On specific features of numerical and experimental investigation of aerodynamic processes at hypersonic flow velocity - Gerasimov, Sergey Ivanovich; Erofeev, Vladimir Ivanovich; Kikeev, Vasiliy Andreevich; Fomkin, Anatoliy Pavlovich (Computational Continuum Mechanics, 2013)
A series of experiments devoted to the estimation of the possibilities of performing aeroballistic tests at hypersonic flow velocities and to the verification of the applied techniques have been performed. The conditions and scheme of experiments as well as the used equipment are described. Experiments were carried out on metal balls made from different materials. The character of the flow around these balls is shown. The dependence of the aerodynamic drag coefficient on the Mach number is shown for different initial velocities. Numerical simulation is conducted in the COSMOSFloWorks software package.